Effect of cholecystokinin on feeding is attenuated in monosodium glutamate obese mice - Maletínská, Lenka; Toma, Resha Shamas; Pirnik, Zdeno; Kiss, Alexander; Slaninová, Jirina; Haluzík, Martin; Zelezná, Blanka (Regulatory peptides, 2006)
Treatment of newborn mice with monosodium glutamate (MSG) is neurotoxic for hypothalamic arcuate nucleus (ARC) and causes obesity. In the MSG-treated 16-week-old NMRI mice, we detected specific ablation of ARC neuronal cells, 8 times higher fat to body mass ratio but unchanged body mass compared to controls, advanced hyperglycemia and hyperinsulinemia--both more pronounced in males, and hyperleptinemia--more severe in females. After fasting, the MSG-treated mice showed attenuated food intake compared to controls. Cholecystokinin octapeptide, which decreased food intake in a dose-dependent manner in 24 h fasted controls, did not significantly affect food intake in the MSG-treated animals. We propose that the obesity-related changes in the feeding behavior of the MSG-treated obese mice were the result of missing leptin and insulin receptors in ARC and consequent altered neuropeptide signaling. This makes the MSG model suitable for clarifying generally the central control of food intake.
Keywords: Neurons; signální transdukce; Cholecystokinin; Male; sexuální faktory; mužské pohlaví; sinkalid; Signal Transduction; Sodium Glutamate; mozek; Mice; Mice, Obese; stravovací zvyklosti; glutamát sodný; Hypothalamus; Brain; hypothalamus; ženské pohlaví; cholecystokinin; zvířata; Cholagogues and Choleretics; Sex Factors; neurony; myši; Feeding Behavior; cholagoga a choleretika; Sincalide; Female; myši obézní; Animals